2006
DOI: 10.1634/theoncologist.11-6-574
|View full text |Cite
|
Sign up to set email alerts
|

Primary Systemic Therapy of Breast Cancer

Abstract: Primary systemic therapy (PST) or neoadjuvant therapy is used in nonmetastatic breast cancer to treat systemic disease earlier, decrease tumor bulk ideally to a complete pathological response (pCR), and reduce the extent of surgery. The multitude of clinical trials using PST in breast cancer patients has not proven the fundamental hypotheses of improved overall survival and disease-free survival that drove the investigation of PST. The other potential advantages of PST, which include increasing the rate of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 108 publications
(128 reference statements)
3
91
0
9
Order By: Relevance
“…21 As an example of how the regimen and duration of therapy impacts pCR, in trials of neoadjuvant for breast cancer, 4 cycles of chemotherapy reportedly achieves pCR ranging from 4% to 13%. 27 With the addition of sequential therapy to a noncross-resistant regimen and up to 6 months of therapy, the pCR rate was reported to be 26% to 31%. 27 The pathologic outcome and surgical morbidity in the current study were similar to other high-risk series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 As an example of how the regimen and duration of therapy impacts pCR, in trials of neoadjuvant for breast cancer, 4 cycles of chemotherapy reportedly achieves pCR ranging from 4% to 13%. 27 With the addition of sequential therapy to a noncross-resistant regimen and up to 6 months of therapy, the pCR rate was reported to be 26% to 31%. 27 The pathologic outcome and surgical morbidity in the current study were similar to other high-risk series.…”
Section: Discussionmentioning
confidence: 99%
“…27 With the addition of sequential therapy to a noncross-resistant regimen and up to 6 months of therapy, the pCR rate was reported to be 26% to 31%. 27 The pathologic outcome and surgical morbidity in the current study were similar to other high-risk series. 8,21 In this study, 1 patient experienced rectal injury, which is similar to the rate of 4.2% reported from a similar series of high-risk patients without preoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The BEvacizumab and Trastuzumab Adjuvant Therapy in HER-2-Positive Breast Cancer trial is a multicenter phase III randomized adjuvant trial comparing chemotherapy plus trastuzumab with chemotherapy plus trastuzumab and the anti-VEGF ligand bevacizumab [352]. No efficacy data are available at this time.…”
Section: Trastuzumab Plus Bevacizumabmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (nac) has become the standard treatment in locally advanced breast cancer. It can render surgically inoperable tumours operable or can downstage a primary tumour, allowing for breast-conserving surgery in patients who might have needed a mastectomy at initial diagnosis 5,6 . Several randomized clinical trials have demonstrated no difference in long-term outcome between patients who receive nac and those who receive adjuvant chemotherapy 7,8 .…”
Section: Introductionmentioning
confidence: 99%